(untitled) (Research, Society and Development, 2020)
This article is the State of Knowledge in reference to “Women in sport inside the Federal Institute of Rio Grande do Norte (Instituto Federal do Rio Grande do Norte/IFRN)”. In this perspective, we visited the papers published on IFRN’s Memoria, located in the site https://memoria.ifrn.edu.br on the space of its first page, and , through this, we expanded to: search/editor/IFRN/books. When carrying out the mapping, we made use of the following keywords: “women’s sport”; “women and sport”; “women in sport”; and “women and sport“ (“mulher and esporte”). For the first two terms, the search did not find any results. However, for the last two terms, we encountered three books. Ergo, we downloaded the books which provided us with good results and we created a filter using the following terms: “women and sport” and “women in sport”; as well as just: “women” and “sport”. Afterwards, we defined that this study’s goal was to identify publications on IFRN’s Memoria about the Women in sport inside IFRN. Thus, from the analysis of the obtained data, in quantitative and qualitative ways, we noticed there were not any publications which alluded or debated about women in sport inside IFRN. In conclusion, on account of me being a sportswoman ever since I was a student from this Institution, there is an understanding that sport for Women inside IFRN happens; even though there is a lack of incentive, of investment and of scientific promotion which would promote it.